Microbial coinfection keratitis: clinical spectrum, pathogen distribution, and antimicrobial susceptibility in an 8-year retrospective study - Acosta-González, María F.; Bautista-Hernández, Luis Antonio; Ponce-Angulo, Diana Gabriela; Anaya-Barragán, Fabiola; Bautista-de Lucio, Victor Manuel (Frontiers in Microbiology, 2025)
BackgroundCoinfection keratitis, involving concurrent infections by bacteria and fungi, poses diagnostic and therapeutic challenges. This study aimed to describe the microbiological and clinical characteristics of keratitis co-infections, including prevalence, predisposing factors, treatment and antimicrobial susceptibility profiles, in patients from a tertiary ophthalmology referral center in Mexico City.MethodsThis retrospective and descriptive study analyzed data collected over an 8-year period (2012–2020) following STROBE guidelines. Corneal samples from patients diagnosed with infectious keratitis were cultured. Only cases with confirmed coinfections-defined as the isolation of more than one microorganism-were included. Microbiological identification and antimicrobial susceptibility were analyzed. Clinical data included demographics, risk factors, visual acuity, corneal reepithelialization, and surgical interventions.ResultsA total of 306 microorganisms were isolated from 140 patients. Among them, 109 cases (78%) involved bacterial-bacterial coinfections, and 31 cases (22%) were bacterial-fungal coinfections. Staphylococcus epidermidis was the most frequently isolated bacterial species (28%), and Fusarium was the predominant fungal isolate (52%). Resistance to erythromycin (52%), clindamycin (46%), and fluoroquinolones (35%) were observed, particularly among S. epidermidis isolates. Previous ocular surgery (34%) and diabetes mellitus (20%) were the most common risk factors. Similar dominant species were observed among institutional monomicrobial isolates analyzed for contextual reference.ConclusionThis retrospective and descriptive study characterizes microbial coinfections in infectious keratitis and provides contextual data from microbial cases from the same institution. Coinfection often involves multidrug-resistant organisms and occurs in patients with risk factors such as prior ocular surgery, contact lens use, or diabetes. Early identification and targeted therapy remain essential to improve clinical outcomes.